Selenium hyperaccumulators harbor a diverse endophytic bacterial community characterized by high selenium resistance and plant growth promoting properties - Sura-de Jong, Martina; Reynolds, Ray J. B.; Richterova, Klara; Musilova, Lucie; Staicu, Lucian C.; Chocholata, Iva; Cappa, Jennifer J.; Taghavi, Safiyh; van der Lelie, Daniel; Frantik, Tomas; Dolinova, Iva; Strejcek, Michal; et al. (Frontiers in Plant Science, 2015)
Selenium (Se)-rich plants may be used to provide dietary Se to humans and livestock, and also to clean up Se-polluted soils or waters. This study focused on endophytic bacteria of plants that hyperaccumulate selenium (Se) to 0.5-1% of dry weight. Terminal restriction fragment length polymorphism (T-RFLP) analysis was used to compare the diversity of endophytic bacteria of hyperaccumulators Stanleya pinnata (Brassicaceae) and Astragalus bisulcatus (Fabaceae) with those from related non-accumulators Physaria bellii (Brassicaceae) and Medicago sativa (Fabaceae) collected on the same, seleniferous site. Hyperaccumulators and non-accumulators showed equal T-RF diversity. Parsimony analysis showed that T-RFs from individuals of the same species were more similar to each other than to those from other species, regardless of plant Se content or spatial proximity. Cultivable endophytes from hyperaccumulators S. pinnata and A. bisulcatus were further identified and characterized. The 66 bacterial morphotypes were shown by MS MALDI-TOF Biotyper analysis and 16S rRNA gene sequencing to include strains of Bacillus, Pseudomonas, Pantoea, Staphylococcus, Paenibacillus, Advenella, Arthrobacter and Variovorax. Most isolates were highly resistant to selenate and selenite (up to 200 mM) and all could reduce selenite to red elemental Se, reduce nitrite and produce siderophores. Seven isolates were selected for plant inoculation and found to have plant growth promoting properties, both in pure culture and when co-cultivated with crop species Brassica juncea (Brassicaceae) or M. sativa. There were no effects on plant Se accumulation. We conclude that Se hyperaccumulators harbor an endophytic bacterial community in their natural seleniferous habitat that is equally diverse to that of comparable non-accumulators. The hyperaccumulator endophytes are characterized by high Se resistance, capacity to produce elemental Se and plant growth promoting properties.